PSXIII-15 Impact of forage allowance on performance and reproductive parameters in Nellore heifers. (8th October 2021) - Ferreira, Igor M; Cidrini, Iorrano A; Oliveira, Karla; Sousa, Luciana; Prados, Laura F; Moretti, Matheus; Siqueira, Gustavo; Resende, Flávio
Abstract: The objective was to evaluate the effects of forage allowance on the performance and pregnancy rate of Nellore heifers submitted to the fixed-time artificial insemination (FTAI) at 14±1 months. The experimental period was divided into the growing phase (GP; 173d) and breeding season (83d). Ninety weaned Nellore heifers [169±19 kg of body weight (BW); 210±28 days of age] were blocked by initial BW and randomly assigned to receive different forage allowance: (1) High (HFA; 7.17 kgDM/kgBW; and (2) Low (LFA; 3.27 kgDM/kgBW); and divided into 6 paddocks (2.15 to 2.4 ha each one). The grazing method used was continuous stocking with a variable stocking rate where treatment conditions were established varying the stocking rate on pasture (put-and-take). The supplement consisted of corn, soybean meal, urea, monensin, sodium chloride and minerals mix (80% TDN and 24% CP) and was provided daily (ad libitum; expected intake around 1% of BW). The final pregnancy rate was determined after two FTAI (d256). Heifers BW at the end of the GP was greater (P < 0.01) for HFA vs. LFA (268 vs. 255 kg). The overall average daily gain (ADG) was greater 68 g/d for animals maintained in HFA than LFA (P < 0.01; 0.713 vs. 0.645 kg/d). Supplement intake (kg/animal/d) had no treatment effect (P = 0.117). On d173, forage allowance affected (P < 0.01) the backfat thickness obtained by real-time carcass ultrasound (HFA = 3.08 vs. LFA = 2.85 mm). The pregnancy rate had no treatment effect (P = 0.223; on average 61%). However, the pregnant heifers per hectare had treatment effect (P = 0.036; HFA = 3.78 vs. LFA = 2.72 pregnant heifers/ha). In conclusion, the low forage allowance reduces the animal performance and affects the carcass composition but provides a greater number of pregnant heifers per hectare.